First record of Luffia Lapidella (Goeze, 1783) in Slovenia (Lepidoptera: Psychidae) - Rekelj, Jurij (Acta entomologica slovenica (Ljubljana), 2013)
Recent studies of Psychidae in Slovenia have resulted in the finding of Luffia lapidella (Goeze, 1783), which is new to Slovenian fauna. Two seasons observation of life cycle at different localities confirmed that the colonies above Dragonja, Socerb and Goriška Brda belong to the parthenogenetic form ferchaultella (Stephens, 1850). Some information about biology and ecology of the species are given.
Keywords: fauna; favna; Lepidoptera; Luffia lapidella; metulji; new record; nova najdba; Psychidae; Slovenia; Slovenija